Effect of the Dimethylformamide/Isopropanol Solvent Ratio on the Structure, Optical Properties, and Photodegradation Performance of RhB Using Bi-MOF - Bui Bao Long, Pham; Nguyen, Van Cuong; Pham, Hoang Ai Le; Ta, Qui Thanh Hoai; Dang, Huu Phuc (Bulletin of Chemical Reaction Engineering & Catalysis, 2025)
This study investigated the structural characteristics, surface morphology, and photocatalytic activity of bismuth-based metal-organic frameworks (BiBTC-ISOx) synthesized with varying ratios of N, N-dimethylformamide (DMF) and isopropanol (ISO). X-ray diffraction confirmed the crystalline structure of the BiBTC-ISOx (x = 1, 3, 6) compounds, while FTIR spectroscopy verified the successful bonding between the ligand and the Bi3+ complex. UV-Vis spectroscopy revealed strong UV light absorption with tunable bandgaps ranging from 3.28 to 3.68 eV. Nitrogen adsorption/desorption analysis revealed a hierarchical micro/mesoporous structure, with BiBTC-ISO6 exhibiting the highest surface area (24.968 m2/g). SEM imaging revealed a rectangular rod-like morphology, which became more elongated with increasing ISO content. The photocatalytic activity of BiBTC-ISOx was evaluated based on the degradation of Rhodamine B (RhB) under visible light, with BiBTC-ISO6 demonstrating the highest efficiency. Optimal conditions for RhB degradation were determined to be 0.03 g catalyst mass, 10 ppm RhB concentration, and pH of 3. Mechanistic studies revealed that superoxide radicals are the primary active species in the photocatalytic process. The BiBTC-ISO6 catalyst exhibited excellent stability and reusability over three consecutive degradation cycles, highlighting its potential for practical applications in organic dye removal. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).